The Development of a training package to enhance the knowledge and skills of teachers and nannies with disabilities In the production of Islamic education media for children with disabilities - หะยียามา, ภาวันตี; แวอุเซ็ง, นิเลาะ (Al-HIKMAH Journal, 2022)
Children with disabilities consider as vulnerable groups that need greatly special cares. However, there is still a lack of Islamic education materials especially for Muslim disable students. This research aims: 1) to develop creating Islamic education media skills for children with disabilities for teachers and babysitters in Service Units under the Special Education Centers, Pattani Province, 2), to compare the teachers and babysitters achievement engaging before and after the training, and 3), to evaluate the satisfaction with the training on creating Islamic education media for children with disabilities. The sample used in this research were 10 teachers and babysitters at the Special Education Service Center, Pattani province, selected by using a purposive sampling method. The research tools comprised of problem condition and training needs assessment questionnaire, media creation skills observation form, training materials on media creation, pre-post test of the training skills, and the satisfaction questionnaire. The data were analyzed using percentage, mean and standard deviation. The research results reveal that :1) After get trained, teachers and babysitters’ s knowledge, understanding and media creation skills, overall, were at the highest level ( = 4.65), when considered individually, it was found that the samples had the level of knowledge, understanding and media-making skills at the highest level ( = 4.40 – 4.90), 2) the comparative result of the achievement ascending from development after training was higher than before the training, and 3)the results of the satisfaction assessment of the sample group towards training on creating media in 3dimesion as follows: input factors were initiated the satisfaction level was the highest ( = 4.81), when measured individually, it was found that the level of opinion was at the highest level for all items ( = 4.60 – 5.00), process factors were established the satisfaction level was at the highest level ( = 4.80), when considered individually, it was found that the level of opinion was at the highest level for all items ( = 4.70 – 5.00), and output factors were originated at the highest level of satisfaction ( = 4.86), when considered individually, it was found that the level of opinion was at the highest level in all of them ( = 4.70 – 5.00).